Intracellular origin and ultrastructure of platelet-derived microparticles - Ponomareva, A. A. (J Thromb Haemost, 2017)
BACKGROUND: Platelet-derived microparticles comprise the major population of circulating blood microparticles that play an important role in hemostasis and thrombosis. Despite numerous studies on the (patho)physiological roles of platelet-derived microparticles, mechanisms of their formation and structural details remain largely unknown. OBJECTIVES: Here we studied the formation, ultrastructure, and composition of platelet-derived microparticles from isolated human platelets, either quiescent or stimulated with one of the following activators: arachidonic acid, ADP, collagen, thrombin, or calcium ionophore A23187. METHODS: Using flow cytometry, transmission and scanning electron microscopy, we analyzed the intracellular origin, structural diversity, and size distributions of the subcellular particles released from platelets. RESULTS: The structure, dimensions, and intracellular origin of microparticles depend on the cell-activating stimulus. The main structural groups include a vesicle surrounded by one thin membrane or multivesicular structures. Thrombin, unlike other stimuli, induced formation of microparticles not only from the platelet plasma membrane but also from intracellular structures. A fraction of these vesicular particles having an intracellular origin contained organelles, such as mitochondria, glycogen granules, and vacuoles. The size of platelet-derived microparticles depended on the nature of the cell-activating stimulus. CONCLUSION: The results obtained provide a structural basis for the qualitative differences of various platelet activators, for specific physiological and pathological effects of MPs, and for development of advanced assays.